Isolation and characterization of two cellulose morphology mutants of Gluconacetobacter hansenii ATCC23769 producing cellulose with lower crystallinity. - Ying Deng; Nivedita Nagachar; Lin Fang; Xin Luan; Jeffrey M Catchmark; Ming Tien; Teh-hui Kao (PLoS ONE, 2015)
Gluconacetobacter hansenii, a Gram-negative bacterium, produces and secrets highly crystalline cellulose into growth medium, and has long been used as a model system for studying cellulose synthesis in higher plants. Cellulose synthesis involves the formation of β-1,4 glucan chains via the polymerization of glucose units by a multi-enzyme cellulose synthase complex (CSC). These glucan chains assemble into ordered structures including crystalline microfibrils. AcsA is the catalytic subunit of the cellulose synthase enzymes in the CSC, and AcsC is required for the secretion of cellulose. However, little is known about other proteins required for the assembly of crystalline cellulose. To address this question, we visually examined cellulose pellicles formed in growth media of 763 individual colonies of G. hansenii generated via Tn5 transposon insertion mutagenesis, and identified 85 that produced cellulose with altered morphologies. X-ray diffraction analysis of these 85 mutants identified two that produced cellulose with significantly lower crystallinity than wild type. The gene disrupted in one of these two mutants encoded a lysine decarboxylase and that in the other encoded an alanine racemase. Solid-state NMR analysis revealed that cellulose produced by these two mutants contained increased amounts of non-crystalline cellulose and monosaccharides associated with non-cellulosic polysaccharides as compared to the wild type. Monosaccharide analysis detected higher percentages of galactose and mannose in cellulose produced by both mutants. Field emission scanning electron microscopy showed that cellulose produced by the mutants was unevenly distributed, with some regions appearing to contain deposition of non-cellulosic polysaccharides; however, the width of the ribbon was comparable to that of normal cellulose. As both lysine decarboxylase and alanine racemase are required for the integrity of peptidoglycan, we propose a model for the role of peptidoglycan in the assembly of crystalline cellulose.